A Multidisciplinary Infection Control Bundle to Reduce the Number of Spinal Cord Stimulator Infections. Issue 6 (24th January 2017) - Yusuf, Erlangga; Bamps, Sven; Thüer, Bénédicte; Mattheussen, Jan; Ursi, Jean‐Paul; Del Biondo, Elke; de Smedt, Kris; Van Paesschen, Raf; Berghmans, Dirk; Hofkens, Kaat; Van Schaeren, Jef; van Havenbergh, Tony; et al.
Abstract : Objective: To investigate the effect of a quality improvement project that resulted in an infection control bundle to reduce the number of spinal cord stimulator (SCS) infections. Materials and Methods: The study was performed in a single center for neuromodulation from January 1, 2014, through May 31, 2016. In response to a high number of surgical site infections (SSIs) after SCS surgery, a multidisciplinary team analyzed the surgical process and developed an infection prevention bundle consisting of five items: 1) showering and decolonization for five days prior to surgery and showering in the hospital on the morning of surgery; 2) performing the SCS implantation as the first in the daily operating room (OR) program; 3) maintaining a minimal number of people in the OR; 4) providing home care nurses with a folder with SCS wound care instructions including pictures; 5) giving oral specific wound care instructions to patients. The number of infections was calculated for the baseline, implementation, and sustainability phases. Results: A total of 410 SCS surgeries were performed during the study period. In the preintervention phase, 26/249 (10.4%) SCS surgeries were infected. During the implementation and sustainability phase, 2/59 (3.4%) and 1/102 (1.0%) SCS surgeries were infected, respectively. The reduction in the number of infections in pre and postintervention phase was statistically significant ( p  = 0.003). Conclusion: Multidisciplinary measures to reduce SSIs reduced the number of SCS associated infections in our study setting.